1987
DOI: 10.1099/0022-1317-68-3-715
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Glycoproteins Associated with Different Morphological Entities Projecting from the Virion Envelope

Abstract: SUMMARYSpikes of different kinds, distinct in size and appearance were detected on the surfaces of herpes simplex virions by electron microscopy of negatively stained preparations. Use of monoclonal antibodies coupled to colloidal gold permitted identification of viral glycoproteins present in different structures projecting from the virion envelope. Antibodies specific for the glycoprotein designated gB bound to the most prominent spikes, which were about 14 nm long and, in side view, had a flattened T-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 16 publications
6
68
0
2
Order By: Relevance
“…Finally, observations similar to the glycoprotein clustering of Fig. 3D had been reported for HSV-1 by immunogold electron microscopy (Stannard et al 1987).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, observations similar to the glycoprotein clustering of Fig. 3D had been reported for HSV-1 by immunogold electron microscopy (Stannard et al 1987).…”
Section: Discussionsupporting
confidence: 88%
“…At the present resolution of our cryoET reconstructions, it was not possible to discern whether there are several distinct types of glycoproteins on the viral envelope, similar to the gB, gC and gD proteins of HSV-1 (Grunewald et al 2003;Stannard et al 1987). Sequence analysis and mass spectrometry studies had identified at least five glycoproteins associated with MHV-68 virion, gB (Bortz et al 2003), gH, and glycoprotein 150 (gp150) with apparent molecular weights of 105kDa, 83kDa, and 150kDa, respectively, as well as glycoproteins encoded by the ORF27 and ORF28 genes (Bortz et al 2003;.…”
Section: Discussionmentioning
confidence: 88%
“…Previously we have successfully employed colloidal gold 0000-8833 © 1989 SGM probes for the identification of three morphologically distinct glycoprotein structures on the envelopes of herpes simplex virus (Stannard et al, 1987) and also for the detection and recognition of the major glycoprotein (gp52) of HCMV (Stannard et al, 1989). It was therefore of interest to use similar immunogold techniques in an attempt to establish the morphological nature of the fl2m-binding site.…”
mentioning
confidence: 99%
“…Colloidal gold particles of approximately 4 nm were prepared as previously described (Stannard et al, 1987) and coupled to fl2m purified from human urine (Sigma) at a pH of 5.8. HCMV strain AD169 was propagated in human embryo fibroblasts (HEF) grown in MEM containing 4~ foetal calf serum (FCS).…”
mentioning
confidence: 99%
“…3) Antibodies to these highly Neuro invasive viruses, Human Herpes Virus 1 & 2, Cytomegalovirus HH5 are found to be the most prevalent and weak. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Cytomegalovirus-infected endothelial cells recruit neutrophils by the secretion of C-X-C chemokines and transmit virus by direct neutrophil-endothelial cell contact during neutrophil transendothelial migration. 32 Therefore, the neuro viral pathology of the heart disrupts the performance of the myocardium and lead to the hypertension and other electrophysiological dysfunctions.…”
Section: Axonal Lesionmentioning
confidence: 99%